Analisis Pengaruh Transmisi Kebijakan Moneter Dan Kinerja Likuiditas Terhadap Kebijakan Struktur Modal Bank Syariah Di Indonesia - Ali Muhayatsyah; Husni Kamal (ITB AAS INDONESIA Surakarta, 2023)
This study examines the policy capital structure of Islamic banks in Indonesia by examining the impact of monetary policy transmission and liquidity performance to the capital structure policies of Islamic banks in Indonesia; The research data used in this study are from the monetary performance of Bank Indonesia and the Sharia Banking Statistics of the Financial Services Authority for the monthly observation period from 2017 to 2021. Multiple linear regression is used to analyze data. The study's findings demonstrate that while the exchange rate and the BI Rate have a sizable negative impact on the debt to equity ratio, the transmission process of monetary policy through inflation variable indicators has a positive impact on that ratio. Influencing capital structure policies in Islamic banking is strongly tied to the transmission of monetary policy in inflation targeting and the stability of the rupiah exchange rate. The capital structure policy of Indonesia's Islamic commercial banks has little impact on liquidity performance as measured by the Minimum Statutory Reserves indicators, Bank Indonesia Sharia Certificates, Cash Ratio, and Financing to Deposit Ratio. This is so that debt-increasing liquidity issues may be avoided by maintaining significantly higher liquidity performance by Islamic Commercial Banks.